Evidence for multi-decadal fuel buildup in a large California wildfire from smoke radiocarbon measurements - A Odwuor; C C Yañez; Y Chen; F M Hopkins; A Moreno; X Xu; C I Czimczik; J T Randerson (Environmental Research Letters, 2023)
In recent decades, there has been a significant increase in annual area burned in California’s Sierra Nevada mountains. This rise in fire activity has prompted the need to understand how historical forest management practices affect fuel composition and emissions. Here we examined the total carbon (TC) concentration and radiocarbon abundance (Δ ^14 C) of particulate matter (PM) emitted by the KNP Complex Fire, which occurred during California’s 2021 wildfire season and affected several groves of giant sequoia trees in the southern Sierra Nevada. During a 26 h sampling period, we measured concentrations of fine airborne PM (PM _2.5 ), as well as dry air mole fractions of carbon monoxide (CO) and methane (CH _4 ), using a ground-based mobile laboratory. We also collected filter samples of PM _2.5 for analysis of TC concentration and Δ ^14 C. High correlation among PM _2.5 , CO, and CH _4 time series confirmed that our PM _2.5 measurements captured variability in wildfire emissions. Using a Keeling plot approach, we determined that the mean Δ ^14 C of PM _2.5 was 111.6 ± 7.7‰ ( n = 12), which was considerably enriched relative to atmospheric carbon dioxide in the northern hemisphere in 2021 (−3.2 ± 1.4‰). Combining these Δ ^14 C data with a steady-state one-box ecosystem model, we estimated that the mean age of fuels combusted in the KNP Complex Fire was 40 years, with a range of 29–57 years. These results provide evidence for emissions originating from woody biomass, larger-diameter fine fuels, and coarse woody debris that have accumulated over multiple decades. This is consistent with independent field observations that indicate high fire intensity contributed to widespread giant sequoia mortality. With the expanded use of prescribed fires planned over the next decade in California to mitigate wildfire impacts, our measurement approach has the potential to provide regionally-integrated estimates of the effectiveness of fuel treatment programs.